Are persons with disabilities included in the Colombian peace process? (2023)
This article follows on from our previous one about the armed conflict in Colombia and its relationship with disability. We seek here to explore the ways in which people with disabilities are starting to be involved in the peace process with the Revolutionary Armed Forces of Colombia–People’s Army (FARC-EP), and the avenues there are for representative organizations of disabled people to have a louder voice in Colombia. Currently, while legal and human rights approaches are important, people with disabilities in Colombia do not generally have the resources to fight for their own rights. However, there could be opportunities in the negotiations currently with the National Liberation Army (ELN) to include a specific focus on the rights of people with disabilities. © 2018 Informa UK Limited, trading as Taylor & Francis Group.